Azziy Boutique Chalet / Nurul Izatie Zainal Akmar … [et al.] - ZAINAL AKMAR, NURUL IZATIE; AZMAN, SAIDATUL NUR ATIEKA; YA'ACOUB, ZAIZURA; ZULKIFLY, ZUREEN ATIEQA; ISHAK, HAYATI (2018)
Azziy Boutique Chalet by Azziy Enterprise is an intimate chalet that is uniquely designed and is dedicated to providing a warm and comfortable personalized service with a special attention to detail.